Silvopasture offers climate change mitigation and profit potential for farmers in the eastern United States - Greene, Harry; Kazanski, Clare E.; Kaufman, Jeremy; Steinberg, Ethan; Johnson, Kris; Cook-Patton, Susan C.; Fargione, Joe (Frontiers in Sustainable Food Systems, 2023)
Silvopasture—integrating trees, forage, and grazing livestock on the same piece of land—is increasingly popular, given its potential to store carbon (C) and improve farmers’ livelihoods. We examined the C and economic implications of adding different silvopastoral systems to existing pastures in historically forested areas of the eastern United States (U.S.). We assessed nine distinct systems, varying by species and product (timber, nuts, and fodder for livestock), for two market scenarios: one based on current demand and one that assumes increased demand for products from silvopasture systems. For each system, we assessed C storage (biomass) and economics (internal rates of return (IRR) with and without C payments). We find that silvopasture in the eastern U.S. could expand by 5.6–25.3 million hectares under base case and full adoption scenarios (equaling a 6% increase in the global footprint of silvopasture), and could capture up to 4.9 or 25.6 Tg CO2e yr.−1, respectively. Expansion of silvopasture in these scenarios would come largely from demand for fodder as a supplemental feed, as well as specialty timber products. Per ha mitigation potential varied widely (0.5–6.5 tCO2e ha−1 yr.−1), due to species differences in C accumulation rates. Economics differed too, with some systems offering short break-even timelines (e.g., 7–9 years for fodder systems), and others costing more up front but having greater long-term returns (e.g., Chestnut). Furthermore, while some systems are profitable without any price on C (e.g., fodder-based silvopasture offers 6–14% 10-year IRRs without a price on C), higher payments for C would likely be necessary to unleash broad investment in timber and nut-based silvopasture. Our analysis included planting, maintenance, and harvest costs and tree product revenue. Future work is needed to fully incorporate additional considerations, like loss of grazing use during establishment, shade-induced effects on forage production, and livestock productivity. Furthermore, specific economic, ecological, site- and operation-level considerations are critical to evaluate the appropriateness of silvopasture systems for a given setting. This analysis suggests that across the eastern U.S., silvopasture could offer both climate change mitigation and enhanced profitability for farmers, with notable differences in the system-specific magnitude of opportunity.